PENGARUH TANGGAPAN DETEKTOR KAMERA GAMMA SPECT PADA PEMERIKSAAN GINJAL - Arifin, Zaenal; Soejoko, Djarwani S (BERKALA FISIKA, 2013)
In nuclear medicine, it is common to exam by using SPECT / SPECT-CT for planar ortomographic imaging. SPECT aircraft can be equipped with one or more detectors. The studyaims to determine the response to the two detectors in SPECT gamma cameras. Furthermore, eachdetector used for renal function. The study consisted of two phases, the first to determine theresponse of each detector using acrylic phantom and the source of Technetium-99m activity of1mCi to 25 mCi. The second stage, renal function tests with planar imaging in four patients usingdetector 1 and detector 2. Acrylic phantom measurement results show the detector response 1 wasrelatively higher. Although the detector 2 has a lower response but is still linear with respect to the activity. In the examination of the kidneys, the evaluation focused on image analysis, count rate, uptake, GFR and transit function of time. The fourth image shows the patient count rate ofdetector 1 is also relatively high. Left kidney uptake value detection results both detectors showedno significant differences, with a mean value (48.3 ± 3.9)% and (51.7 ± 2.2)% for detector 1 anddetector 2. Both detectors generate GFR values in all four patients were in the range of 58-96 ml /min of detector 1 and 75-98 ml / min of detector 2. The results of these two detection detectortransit time function shows the left kidney patients in all phases of the four showed no significantdifferences. It was concluded that the two detectors have relatively low response but is still linearwith respect to the activity. Therefore detector 2 can still provide diagnoses did not differsignificantly with detector 1.Keywords : SPECT, Technetium-99m, response of detector, Examination of Renal